Acronyms: a Representation of Language Play - Maricar, Farida (CV. Eureka Murakabi Abadi, 2024)
This paper describes the use of acronyms in our daily activities, both in speaking and in writing. Acronyms are pervasive and created in various ways by different individuals. Language is used as the primary means of communication. Sometimes, it is simplified or set in various ways to make it easy to be spoken. This is qualitative descriptive research. Data were from speech and writing in the case of acronyms. Data then were collected by note taking. The technique of analyzing data was the matching technique. This research found that people use acronyms to show their ability in playing the language beside to make the word more efficient. This phenomenon is influenced by the sociolinguistic conditions of the community.